Solve 2*c + 2*d - 6 + 0 = 0, -3*c + d = -1 for c.

1

Solve -14 = 43*g - 45*g + 4*x, -4*g + 14 = -x for g.

3

Solve -3*a - 3*j = 3, 4*a = -3*j + 2*j - 7 for a.

-2

Solve -3*h - 4*o = -2, -4*h + 13 = h - 3*o for h.

2

Solve -6 = -5*c + y - 1, c + y = 1 for c.

1

Solve -5*i - 5 = -5*d, -3*d + 3 = -19*i + 18*i for i.

0

Solve 6*d - 10*d = 2*m + 30, 0 = -m - 3*d - 20 for m.

-5

Solve 6*r = 3*i + 11*r + 39, 2*i + 1 = 5*r for i.

-8

Solve -60*x + 4*p = -63*x + 20, -4*x + 2*p + 12 = 0 for x.

4

Solve 4*h - 32 = 4*g, 4*h - 6*h = g - 1 for h.

3